2003
DOI: 10.1063/1.1563258
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dynamics in a model of the turbulent buffer layer

Abstract: A Brownian dynamics study of bead-spring-chain polymer dynamics is undertaken in a model flow that captures key features of the buffer region of near-wall turbulence-wavy streamwise vortices superimposed on a mean shear. In this flow and in any Lagrangian chaotic flow, a Hookean dumbbell polymer will stretch indefinitely if and only if the Weissenberg number based on the largest Lyapunov exponent for the velocity field is у 1 2 . In the flow investigated here, this criterion is found to be good predictor of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 40 publications
6
46
0
Order By: Relevance
“…To address this point, we have previously compared FENE-P to more realistic bead-spring-chain models for calculating the stresses in the flow field of a Couette flow ECS. 44 We performed Brownian dynamics simulations of 20-spring chains, with hydrodynamic and excluded volume interactions among the polymer segments explicitly included, as they moved along Lagrangian trajectories in the ECS. Comparing the FENE-P results to the "exact" results from the chain models, we found that the FENE-P model qualitatively captured the spatial variations in polymer stress.…”
Section: Mathematical Formulation and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this point, we have previously compared FENE-P to more realistic bead-spring-chain models for calculating the stresses in the flow field of a Couette flow ECS. 44 We performed Brownian dynamics simulations of 20-spring chains, with hydrodynamic and excluded volume interactions among the polymer segments explicitly included, as they moved along Lagrangian trajectories in the ECS. Comparing the FENE-P results to the "exact" results from the chain models, we found that the FENE-P model qualitatively captured the spatial variations in polymer stress.…”
Section: Mathematical Formulation and Simulation Detailsmentioning
confidence: 99%
“…(This process of polymer molecules stretching in the streaks and relaxing at the edges of the vortices is also confirmed by Brownian dynamics simulations of model polymers along a Lagrangian trajectory in the ECS. 44 ) The result of this process of stretching and relaxation of the polymer is a region of high polymer stress in the streamwise streak and a region of lower polymer stress where fluid elements have left the streaks and begun to move around one of the vortices. Taking the divergence of the polymer stress gives a force due to the polymer that is directly opposed to the movement of fluid into the vortex.…”
Section: Given Whatmentioning
confidence: 99%
“…6). It is tempting to speculate that they are fingerprints of the coherent structures characterizing the flow close to the wall (Nagata 1990;Busse 1992, 1997;Eckhardt 1997, 2000;Eckhardt et al 2002;Stone and Graham 2003) whose relative strength might be influenced by the polymer concentration (De Angelis et al 2003). A further detailed investigation of this phenomenon is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is straightforward to show (see e.g. (Lumley, 1972;Stone and Graham, 2003;Balkovsky et al, 2000Balkovsky et al, , 2001Chertkov, 2000)) that, for a Hookean dumb- …”
Section: Existence Of the Ecsmentioning
confidence: 99%
“…In prior work, our group has studied the initial effects of viscoelasticity on ECS in the plane Couette geometry (Stone et al, 2002;Stone and Graham, 2003;Stone et al, 2004).…”
Section: Introductionmentioning
confidence: 99%